MR defecography detects pelvic floor dysfunction in participants with chronic complete spinal cord injury - Putz, Cornelia; Alt, Céline D.; Wagner, Björn; Gantz, Simone; Gerner, Hans-Jürgen; Weidner, Norbert; Grenacher, Lars; Hensel, Cornelia (Spinal cord, 2020)
A prospective single arm study. Previously we have demonstrated that magnetic resonance (MR) defecography is feasible in participants with complete spinal cord injury (SCI). The main aim of this study is to evaluate whether MR defecography can provide objective parameters correlating with the clinical manifestations of neurogenic bowel dysfunction (NBD) in participants with SCI. A monocentric study in a comprehensive care university hospital Spinal Cord Injury Center. Previously published MR defecography parameters (anorectal angle (ARA), hiatal descent (M-line) and hiatal width (H-line)) of twenty participants with SCI were now compared to a standardized clinical assessment of NBD. Descriptive statistics, correlations and t-tests for independent samples were calculated. The significantly higher values for the ARA at rest and M-line at rest in participants with SCI correlated with the clinical assessment of bowel incontinence. Furthermore, in nearly half of the investigated SCI cohort the normally positive difference between ARA, M-line and H-line at rest and during defecation became negative suggesting pelvic floor dyssynergia as a potential mechanism underlying constipation in people with complete SCI. In fact, these participants showed a more severe clinical presentation of NBD according to the total NBD score. MR defecography provides objective parameters correlating with clinical signs of NBD, such as constipation and bowel incontinence. Therefore, MR defecography can support pathophysiology-based decision-making with respect to specific therapeutic interventions, which should help to improve the management of NBD.